KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN SOAL OPERASI HIMPUNAN - Yantina Leba Djawa; Elsy Senides Hana Taunu; Mega Retno Wulandari; Yuliana Tamu Ina Nuhamara; Stevvileny Angu Bima; Iona Lisa Ndakularak (Program Studi PGSD Universitas Flores, 2022)
This study aims to describe critical thinking skills, identify factors that affect critical thinking skills and recommend follow-up plans to overcome students' low critical thinking ability to complete class VII set operations problems at Waingapu City Junior High School. This type of research is descriptive research with a qualitative approach. Data collection uses tests, interviews and documentation studies. The subjects in the study were 30 students of class VII junior high school in Waingapu City. The results found that the average critical thinking ability of students was 37.29 and was in the low category. There are several factors that affect students' critical thinking skills, including lack of relearning of the material that has been obtained, mastery of mathematical concepts, learning interests and students' thoroughness in working on problems. The recommendations of actions taken by teachers are reviewing the basic concepts of mathematics, designing learning devices and training students to work on story problems and learning motivation.